IMPLEMENTASI ALGORITMA LINEAR CONGRUENT METHOD (LCM) PADA MEDIA PEMBELAJARAN BAGIAN-BAGIAN BUNGA BERBASIS VIRTUAL REALITY (Studi Kasus : SMP Negeri 2 Ciawigebang) - Rio Andriyat Krisdiawan; Heru Budianto; Tata Sutabri; Ade Kurniawan (NUANSA INFORMATIKA, 2022)
SMP Negeri 2 Ciawigebang is one of the schools that also uses books as the main source of learning references. The use of books has limitations, especially in the content of the existing 2-dimensional images, the images on the textbook will fade over time, which makes it difficult for students to understand and has limited visualization of the material. Learning that is carried out online due to the impact of the COVID-19 pandemic and books as independent learning media result in ineffective understanding of the material to students. Therefore, we need media with the use of technology that can visualize materials, visualizations and objects that help students understand in independent learning such as virtual reality (VR). Virtual reality is a sophisticated human-computer interface that simulates a realistic environment and allows the user to interact directly with the simulated object. To find out the extent to which students are able to absorb the material given, an evaluation is carried out in the form of the questions that are given, therefore a Linear Congruent Method algorithm is used to randomize the questions, so that there is no repetition of the same questions that are raised. While the system development method used is the Multimedia Development Life Cycle (MDLC) as the right method for developing AR-based learning media. The final result of this research is an application that is compatible with smartphone devices with a minimum Android operating system Nougat version. which displays objects in the form of 3-dimensional VR where users feel like they are in a virtual world and questions are given to evaluate the extent to which students can absorb the material. it is hoped that this application can facilitate the learning and teaching process through virtual reality media and make it easier for teachers when delivering material and conducting 3D visual-based evaluations. Keywords: Learning Media, Virtual Reality, Algorithm Linear Congruent Method (LCM)